The Synergistic Effect of Job Satisfaction as A Mediator between Quality of Work Life and Organizational Commitment on Job Performance - Rama Fajar Shidiq; Noekent, Vitradesie; Muhammad Zain Alfain (Management Analysis Journal, 2024)
The purpose of this study was to determine the effect of quality of work life and organizational commitment on job performance with job satisfaction as a mediating variable. The population in this study were the staff of PT Asia Pacific Fibers Kendal. The number of samples used in this study were 211 staff of PT Asia Pacific Fibers Kendal. The data collection method used a questionnaire. The results showed that there is a positive and significant effect of quality of work life and organizational commitment on job performance, but job satisfaction has no significant effect on job performance. The results also show that job satisfaction cannot mediate the effect of quality of work life and organizational commitment. Suggestions that can be given are to conduct gathering and kinship activities that can help staff help each other in completing tasks and companies must provide appropriate responsibilities, authority, and opportunities to staff so that staff feel they have the opportunity to apply various skills that can improve the quality of their work life and organizational commitment